The Academic Senate and University Governance in Canada - Jones, Glen A.; Shanahan, Theresa; Goyan, Paul (Canadian Journal of Higher Education, 2004)
This study examines the academic senate within the context of university governance in Canada. Data were obtained from a survey of university senate secretaries on senate structure, composition, and operation, and from a survey of senate members on their perceptions of the senate, their role as senate members, and the nature of their work. The study raises concerns over the effectiveness of the senate and suggests a need to review the senate and its role in contemporary university governance within the context of the current Canadian higher education environment.